2018
DOI: 10.1016/j.socscimed.2018.06.017
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mobility on HIV-related healthcare access and use for female sex workers: A systematic review

Abstract: Female sex workers (FSW) experience a high HIV burden and are often mobile. FSW access to HIV-related healthcare is essential for equitable welfare and to reduce new HIV infections. We systematically reviewed the literature on mobility and HIV-related healthcare access and use among FSW. Outcome measures included: HIV/STI testing, STI treatment, PrEP (initiation or adherence), and ART (initiation or adherence). We summarised the results with a narrative synthesis. From 7417 non-duplicated citations, nine studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 106 publications
0
22
1
Order By: Relevance
“…As of 2018, adolescents and young adults aged 15 to 24, particularly girls in SSA, have been among the highest risk of HIV infection in the world and are estimated to contribute to nearly 20% of all new infections annually [37]. Immigration and mobility patterns have been an emerging area of research for understanding risk of transmission as well as access to testing and treatment services [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…As of 2018, adolescents and young adults aged 15 to 24, particularly girls in SSA, have been among the highest risk of HIV infection in the world and are estimated to contribute to nearly 20% of all new infections annually [37]. Immigration and mobility patterns have been an emerging area of research for understanding risk of transmission as well as access to testing and treatment services [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated differences in occupation, income, and education level in different populations (5,7,(33)(34)(35)(36) and have demonstrated that migrant populations lack awareness of HIV prevention and treatment (16,37). Therefore, migrant patients are at higher risk of having HIV infection and of spreading the disease.…”
Section: Discussionmentioning
confidence: 99%
“…A previous qualitative study in this cohort reported that participants commonly moved to fishing communities for extended periods in search of clients. 15 These communities have been linked with high HIV prevalence and incidence, yet the fishermen usually preferred condomless sex, thus increasing HIV vulnerabilities for the mobile participants. 33 Other findings in this cohort are a signal to the potential economic pressures facing participants to not only deter them from accessing the much-needed clinic services but also affecting their ability to refuse sex with a client paying more for noncondom use.…”
Section: Structural Factorsmentioning
confidence: 99%
“…[11][12][13] The most commonly identified contextual factors are stigma, discrimination, and criminalization and their associated consequences. [14][15][16] However, other contextual factors such as the high mobility among sex workers have been identified to delay the utilization of services. 16,17 These contextual factors typically act through the individual factors such as perceptions of HIV risk and importance of services as well as behavioral (sexual and substance abuse), reproductive, and biological characteristics (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation